The spontaneous discourse of radio presenters in states of security emergency. (1st October 2018) - Ben-Atar, Ella; Ben-Asher, Smadar
Scholars from various research disciplines have focused on ways of helping a civilian population withstand mass natural or human-instigated disasters. The present study examines the theoretical principles suggested by Hobfoll et al. (safety, calming, efficacy, connectedness and hope) by an analysis of the spontaneous discourse of educational radio presenters during emergency broadcasts when the region's residents live under the constant danger of rocket fire. This study analysed 198 broadcasting hours sampled from three different periods of military conflict (2008−14). The radio presenters' spontaneous discourse was analysed by content, drawing a distinction between resilience-promoting (function) and resilience-impairing (dysfunction) messages. The findings show that despite the presenters' intention to help the community contend with the difficult situation, numerous resilience-impairing messages also appeared in their spontaneous discourse. The present study contributes by providing an additional layer of theoretical research on interventions in community stress situations and looks at utilizing the potential inherent in educational radio as a tool to aid development of community resilience.